Impact of Community-based Adaptation Methods in Creating Resilient Communities in Indonesia and Philippines - Tota Wayne; Abdul Maulud Khairul Nizam; Md Noor Noorashikin (E3S Web of Conferences)
Asian coastal communities have adopted community-based-adaptation (CBA) methods to foster resilience on climate change impacts. In Indonesia, implementation of CBA in communities had a positive resilience score of 35%. Robustness of infrastructure and cohesion in community disaster-preparedness was measured using the standardised resilience index. In a 5 year period, economic-climatic related losses had a 40% decrease. Improvements were observed in disaster management, aquaculture, food, and water-security resilience, thus, 25% water management practices, also including irrigation systems and flood control measures. Effective CBA were exemplified by Climate-Village (Kampung-Iklim) Indonesia where collaborative-governance, public-awareness, and sustainable-practices, increased community participation and improved local environmental conditions. Furthermore, riverbank projects in Philippines included modern techniques integrated with indigenous-knowledge enhanced community-resilience in fisheries and aquaculture, food security and sustainable water management. Community engagement was crucial for successful adaptation, and this led to responsibility and ownership among community members. These adaptation projects improved livelihoods through sustainable agricultural practices and income-generation through diversification. Communities showed sustained resilience due to increased and positive ecological footprint. Flood control structures were observed to increase risk of maladaptation by downstream flooding. This paper focuses on assessing impact of community-based adaptation methods in creating resilient communities in Asia.